The art of loving - Gajowski, Evelyn (Univ. of Delaware Press u.a., 1992)
To be a subject is to be able to speak, to give meaning. The Art of Loving interrogates the phenomenon of
Keywords: Shakespeare; William <1564-1616>; Shakespeare; William; Antony and Cleopatra; Othello; Romeo and Juliet; Sekserol; Tragedies; Frau; Psychologie; Wissen; Drama; Femininity in literature; Love in literature; Sex differences (Psychology) in literature; Subjectivity in literature; Tragedy; Women in literature; Tragödie; Geschlechterverhältnis